Application and CFD-Based Optimization of a Novel Porous Object for Confined Slot Jet Impingement Cooling Systems under a Magnetic Field - Walid Aich; Fatih Selimefendigil; Badreddine Ayadi; Lotfi Ben Said; Badr M. Alshammari; Lioua Kolsi; Sid Ali Betrouni; Hatem Gasmi (Mathematics, 2022)
A novel porous object for the control of the convective heat transfer of confined slot nanojet impingement is offered under magnetic field effects, while optimization-assisted computational fluid dynamics is used to find the best working conditions to achieve the best performance of the system. The flow, thermal patterns, and heat transfer characteristics were influenced by the variation in rotational Reynolds number (Rew), Hartmann number (Ha), permeability of the porous object (Da) and its location (Mx). There was a 14.5% difference in the average Nusselt number (Nu) at the highest Rew when motionless object configuration at Ha = 5 was compared, while it was less than 2% at Ha = 25. At Rew = −600, the average Nu variation was 22% when cases with the lowest and highest magnetic field strength were compared. The porous object provides an excellent tool for convective heat transfer control, while the best performance was achieved by using optimization-assisted computational fluid dynamics. The optimal sets of (Rew, Da, Mx, AR) for porous object were (−315.97, 0.0188, −1.456, 0.235), (−181.167, 0.0167, −1.441, 0.2), and (−483.13, 0.0210, −0.348, 0.2) at Ha = 5, 10, and 25, respectively. At the optimal operating point, the local Nu enhancements were 19.46%, 44.86%, and −0.54% at Ha = 5, 10, and 15, respectively, when the no-object case was compared, while the average values were 7.87%, 8.09% and 5.04%.